Characterization of Spawning Behavior in Cultured Delta Smelt. (21st March 2021) - Tsai, Yi‐Jiun Jean; Chase, Samantha; Carson, Evan W.; Zweig, Leanna; Hung, Tien‐Chieh
Abstract: We examined cultured Delta Smelt Hypomesus transpacificus under laboratory settings to provide the first formal characterization of spawning behavior, which included the quantification of participants and diel spawning patterns. We video recorded behavioral observation trials in which four mature males and four ripe females interacted freely for 9–11 d. We found that three behaviors were consistently associated with egg release: (1) two or more fish swam in close proximity to one another just above the substrate or tank floor, (2) fish swam together synchronously during fast, forward‐swimming movements (bouts) while in tandem and in close proximity to one another, and (3) female(s) released eggs and male(s) presumably released milt during one or more bouts. We also found that two to five fish participated in any given spawn and that spawning occurred at night. Furthermore, spawns were observed across three consecutive nights within a trial and up to 17 times within one night, indicating that individuals spawned serially within and across nights within a single clutch cycle. This study enhances our understanding of the Delta Smelt mating system and informs ongoing conservation efforts.